Physiological concentrations of glucocorticoids induce pathological DNA double‐strand breaks. (7th December 2022) - Akter, Salma; Shimba, Akihiro; Ikuta, Koichi; Mahmud, Md. Rasel Al; Yamada, Shintaro; Sasanuma, Hiroyuki; Tsuda, Masataka; Sone, Masakatsu; Ago, Yukio; Murai, Kenichi; Tanaka, Hisashi; Takeda, Shunichi
Abstract: Steroid hormones induce the transcription of target genes by activating nuclear receptors. Early transcriptional response to various stimuli, including hormones, involves the active catalysis of topoisomerase II (TOP2) at transcription regulatory sequences. TOP2 untangles DNAs by transiently generating double‐strand breaks (DSBs), where TOP2 covalently binds to DSB ends. When TOP2 fails to rejoin, called "abortive" catalysis, the resulting DSBs are repaired by tyrosyl‐DNA phosphodiesterase 2 (TDP2) and non‐homologous end‐joining (NHEJ). A steroid, cortisol, is the most important glucocorticoid, and dexamethasone (Dex), a synthetic glucocorticoid, is widely used for suppressing inflammation in clinics. We here revealed that clinically relevant concentrations of Dex and physiological concentrations of cortisol efficiently induce DSBs in G1 phase cells deficient in TDP2 and NHEJ. The DSB induction depends on glucocorticoid receptor (GR) and TOP2. Considering the specific role of TDP2 in removing TOP2 adducts from DSB ends, induced DSBs most likely represent stalled TOP2‐DSB complexes. Inhibition of RNA polymerase II suppressed the DSBs formation only modestly in the G1 phase. We propose that cortisol and Dex frequently generate DSBs through the abortive catalysis of TOP2 at transcriptional regulatory sequences, including promoters or enhancers, where active TOP2 catalysis occurs during early transcriptional response.